Radulf, en bagmand fra 1100-årene – eller den varme sten i sengen - Madsen, Per Kristian (Kirkehistoriske Samlinger, 2022)
Artiklen har sit udgangspunkt i en klassisk, hundredårig teori i dansk middelalderforskning, nemlig svaret på spørgsmålet om, hvem der hvornår og hvorfra fik bragt teglen til Danmark i 1100-årene. Mere principielt drejer det sig om samspillet mellem historie, kunst- og arkitekturhistorie og bygningsarkæologi, eller om man vil, historie og kulturhistorie. Det vil også fremgå af redegørelsen om den, der i 1924 blev udpeget som bagmand i teglsagen, nemlig Valdemar den Stores sekretær og kansler, Ribes biskop Radulf (død 1171). Summary In 1924 the Danish architect Mogens Clemmensen put forward his theory on the introduction of brick building into Denmark just around 1160. His explanation to this was mainly accepted, by architectural researchers and art historians as well as historians, although also put under discussion. His studies were concentrated on North Italian Lombardic churches and Cistercian abbey churches, pinpointing several architectonic details which he also identified in Danish brick churches from the second part of the 12th century, situated on the island of Seeland. A few sources refer to the use of bricks for defensive works during the reign of king Valdemar the Great (1157-1182). Clemmensen also pointed to the man whom he believed had personally transferred the technique of brick making and building directly from the Lombardy to Denmark. This mastermind was Radulf (died 1171), an Englishman by birth, although his name occurs more than once in 12th century Denmark, and a secretary and chancellor of king Valdemar. According to Clemmensen Radulf attended a synod in Pavia in 1160 on behalf of the king. From there Radulf should have brought the knowledge of bricks and their use back into Denmark. The year 1160 was early enough to fit in with the proposed and very short initial construction period of the Royal Abbey Church of Ringsted and the erection of the Abbey Church of Sorø at the initiative of bishop Absalon, the king’s close friend and prime counsellor. The Pavia meeting was summoned by the Emperor, Frederick Barbarossa. It was a part of the Grand Schism and two years later, Valdemar had to submit to the emperor as his vassal and accepted the crown of his country from the emperor’s hand. Radulf also participated in these events which were described by the Danish historian Saxo who did his very best to hide most of the role of Valdemar and Absalon as followers of the schismatic line of Frederick Barbarossa. He almost accuses Radulf, whom he seems to have disliked, not to have acted to the best of Danish interests. A scrutiny of the available sources, presented in this paper, did not confirm the participation of Radulf in the Pavia meeting, which was instead attended by Elias, whom Radulf followed as a bishop of Ribe from 1162. Elias was Flemish by birth and obviously both prelates made their careers in Denmark due to their international education and skills. Both may have visited the Paris University Schools and maybe Absalon, who was there as a student before 1157, actually met Radulf in Paris. The general idea of a single main ecclesiastical and political figure as Radulf as the mastermind behind the introduction of building materials and specific architectonic ideals represents a somewhat outdated view. Never forget what Abbot Suger wrote about diversity. Instead the rapid spread of building techniques may have followed the intense evolution of urban sites, clusters and trade during the second part of the 12th century, which created the background for the German Hanse and the connections between North West Europe, the Baltic and the Mediterranean. A series of rather elaborated theories concerning the personal artistic views and influences of Radulf followed each other after the initial work of Clemmensen. These ideas were based on his supposed English origin and his activities as a church administrator, a supplier of church relics and as a founder of a Cistercian abbey as well as the possible initiator of the oldest brick building in Ribe, which does not show any similarities with Lombard architecture, however. His seal as a bishop has for long been considered as an English type. The best parallels, however, occur between the seals of Imperial bishops from the time of Radulf’s meeting with the emperor, and whoever did bring the collection of relics in question, most reasonably acquired them somewhere in North Germany, not in England. As for the Cistercian Abbey of Løgum, for which Radulf was a true benefactor, like other fellow bishops, it had its roots in the Abbey of Herrisvad, whose monks came from France. Paris was also the place of inspiration behind a latin sermon of the second half of the 12th century which has survived from Løgum. It was written to a congregation of nuns and carries the name of an author called Radulf. An authorship of the bishop of Ribe remains unproven. On the other hand, the sermon demonstrates a close affiliation with Parisian theological thoughts and publishing.